American art of the 20th century; 839 illustrations including 166 colour plates. - Hunter, S. (London : Thames and Hudson, 1973)
Albers, Josef ; Andre, Carl ; Anuszkiewicz, Richard ; Avery, Milton ; Baziotes, William ; Bearden, Romare ; Bellows, George ; Benton, Thomas Hart ; Blume, Peter ; Brooks, James ; Burchfield, Charles ; Calder, Alexander ; Chamberlain, John ; Cornell, Joseph ; D'Arcangelo, Allan ; Davies, Arthur B. ; Davis, Stuart ; Demuth, Charles ; Diller, Burgoyne ; Dine, Jim ; Dove, Arthur ; Evergood, Philip ; Ferber, Herbert ; Flannagan, John B. ; Francis, Sam ; Frankenthaler, Helen ; Glackens, William ; Glarner, Fritz ; Gorky, Arshile ; Gottlieb, Adolph ; Graves, Morris ; Guston, Philip ; Hartley, Marsden ; Henri, Robert ; Hesse, Eva ; Hofmann, Hans ; Hopper, Edward ; Indiana, Robert ; Johns, Jasper ; Judd, Donald ; Kelly, Ellsworth ; Kienholz, Edward ; Kline, Franz ; Lachaise, Gaston ; Lassaw, Ibram ; LeWitt, Sol ; Levine, Jack ; Lichtenstein, Roy ; Lindner, Richard ; Lipton, Seymour ; Louis, Morris ; Luks, George ; Lye, Len ; MacDonald-Wright, Stanton ; Man Ray ; Marin, John ; Marisol ; Marsh, Reginald ; Maurer, Alfred ; Morris, Robert ; Motherwell, Robert ; Nadelman, Elie ; Nakian, Reuben ; Nauman, Bruce ; Nevelson, Louise ; Newman, Barnett ; Noguchi, Isamu ; Noland, Kenneth ; O'Keeffe, Georgia ; Oldenburg, Claes ; Olitski, Jules ; Pearlstein, Philip ; Pollock, Jackson ; Poons, Larry ; Prendergast, Maurice ; Rauschenberg, Robert ; Reinhardt, Ad ; Rickey, George ; Riverhead (New York) ; Rivers, Larry ; Rosenquist, James ; Roszak, Theodore ; Rothko, Mark ; Samaras, Lucas ; Segal, George ; Serra, Richard ; Shahn, Ben ; Sheeler, Charles ; Shinn, Everett ; Sloan, John ; Smith, David ; Smith, Tony ; Smithson, Robert ; Soyer, Raphael ; Spencer, Niles ; Stella, Frank ; Stella, Joseph ; Still, Clyfford ; Sugarman, George ; Suvero, Mark di ; Tobey, Mark ; Tomlin, Bradley Walker ; etc.
boek